The Influence of Price, Store Atmosphere and Food Product Quality on Buying Interest at Tootor Coffee Takengon - Rayuwati, Rayuwati; Yustisar, Muhamad; Gemasih, Husna; Eliyin, Eliyin (International Journal of Science, Technology & Management, 2022)
This research was conducted at Tootor Coffee Takengon. This study aims to determine how the effect of Price (X1), Store Atmosphere(X2), and Foof Product Quality (X3) on Buying Interest (Y) of Tootor Coffee Takengon Customers. The population in this study is the population in Central Aceh. The sampling technique used is convenience sampling and accidental sampling. With the Lemeshow method, the research sample was 98 respondents. The research was conducted from February to August 2022. Data processing was processed using the SPSS version 25.0 application with multiple linear regression models. Source of data is primary data taken directly from respondents. Based on the results of multiple linear regression analysis using the F test, it can be seen that the product, service quality, price, and store atmosphere variables together influence consumer buying interest at Tootor Coffee Takengon. This can be seen through the obtained Ftest, namely Fcount = 659,591 > Ftable = 1,985. The results of this study indicate that price has the most significant effect on consumer buying interest to eat/drink at Tootor Coffee. These results illustrate that Tootor Coffee is in accordance with what consumers expect, so that consumers feel satisfied and loyal to eat and drink at this café.